2022
DOI: 10.1098/rsta.2021.0144
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis in hybrid perovskite indoor photovoltaics

Abstract: Halide perovskite indoor photovoltaics (PV) are a viable solution to autonomously power the billions of sensors in the huge technology field of the Internet of Things. However, there exists a knowledge gap in the hysteresis behaviour of these photovoltaic devices under indoor lighting conditions. The present work is the first experimental study dedicated to exploring the degree of hysteresis in halide perovskite indoor photovoltaic devices by carrying out both transient J–V scan and steady state maximum power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…Our recent investigation has shown that compared to 1 sun illumination, the halide perovskite photovoltaic devices demonstrate a completely different J – V hysteresis behaviour under indoor lighting conditions, depending on the selection of the device architecture and the photoactive layers. 59 Compared to CH 3 NH 3 PbI 3 , TA devices show slightly greater J – V hysteresis under 1 sun illumination, [Fig. 2(e)].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our recent investigation has shown that compared to 1 sun illumination, the halide perovskite photovoltaic devices demonstrate a completely different J – V hysteresis behaviour under indoor lighting conditions, depending on the selection of the device architecture and the photoactive layers. 59 Compared to CH 3 NH 3 PbI 3 , TA devices show slightly greater J – V hysteresis under 1 sun illumination, [Fig. 2(e)].…”
Section: Resultsmentioning
confidence: 99%
“…S9,† indicating that the Spiro-OMeTAD interface as well as the SnO 2 /perovskite interface are contributing to the J – V hysteresis. 59 However, the photovoltaic performances of P3HT-based devices are consistently lower than Spiro-OMeTAD devices and one contributing factor could be the low conductivity of the undoped P3HT films used as the HTL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the first studies of PSCs under low irradiance conditions was performed by Raifuku et al They demonstrated that PSCs performed better at low irradiance than c-Si solar cells and also that there is room for the optimization of solar cells intended for low light operation. In the following years, research efforts on indoor specific PSCs accelerated, with research groups focusing on electron transport layer optimization and its interface to the perovskite layer, , deposition techniques and the composition of the perovskite layer to improve crystallization and reduce the number of surface and bulk defects, the optimization of J–V hysteresis and consequent PCE improvement. , Skafi et al demonstrated flexible PSCs for indoor use, while Kin et al combined three PSCs connected in series with a sodium-ion battery to construct a very compact nonintermittent renewable power solution for small electronics devices.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the outstanding indoor PV performance, and other potential attributes such as low cost, simple fabrication process, and the fitness for scalable and flexible fabrication, halide perovskite has become one of the most promising candidates for the indoor PV industry. However, our recent investigation has shown that under indoor lighting conditions, halide perovskite PVs demonstrate different J-V hysteresis compared to 1 sun illumination and the extent of deviation depends on the selection of the photoactive layers and the charge transport layers [25]. For the halide perovskite indoor PVs to be reliably employed as an efficient self-powering source for the IoT sensors, the J-V hysteresis needs to be suppressed.…”
Section: Introductionmentioning
confidence: 99%